Life experiences and coping mechanisms among breast cancer patients in an urban Malaysian hospital : a qualitative study - Nour Hanan Daniah MB,; Ahmad Anwaar MS,; Siti Soraya AR,; Zarini I, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Breast cancer is top-ranking cancer that affects the quality of life among women in Malaysia. Although it is very difficult to define the quality of life (QoL) precisely, it has a broad concept that affects global life satisfaction, which includes good health, adequate housing, employment, personal and family safety, interrelationships, education, and leisure pursuits. In this study, we aimed to discuss the life changes upon being diagnosed with breast cancer and their perception of social support. We also discussed the spirituality factor in patients’ coping mechanism with their health condition. This study was carried out using a purposive sampling method. The perception of social support, quality of life, and religiosity factor is discussed through the perspectives of nine breast cancer patients with an interview consisting of semi-structured questions. Basic interpretive qualitative methodology was applied to analyse the perception of social support and religiosity factor as a coping mechanism. The results showed that all the breast cancer patients reported good social support from family and friends except for one patient. Five themes were identified, namely patterns of life, supportive atmosphere, decision making and confidence, expectation, as well as psychological defences and spirituality. Seven out of nine patients reported that their religion helped them to cope with the disease by maintaining self-esteem, providing a sense of meaning and purpose, giving emotional comfort, and providing a sense of hope. In conclusion, social support and religious factor are very important in the lives of breast cancer patients in dealing with their health condition.